Asymmetric Ring‐Opening of Cyclopropyl Ketones with Thiol, Alcohol, and Carboxylic Acid Nucleophiles Catalyzed by a Chiral N, N′‐Dioxide–Scandium(III) Complex. Issue 46 (23rd September 2015) - Xia, Yong; Lin, Lili; Chang, Fenzhen; Fu, Xuan; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly efficient asymmetric ring‐opening reaction of cyclopropyl ketones with a broad range of thiols, alcohols and carboxylic acids has been first realized by using a chiral N, N ′‐dioxide–scandium(III) complex as catalyst. The corresponding sulfides, ethers, and esters were obtained in up to 99 % yield and 95 % ee . This is also the first example of one catalytic system working for the ring‐opening reaction of donor–acceptor cyclopropanes with three different nucleophiles, let alone in an asymmetric version. Abstract : The highly efficient title reaction supplied a variety of chiral sulfides, ethers, and esters in excellent outcomes (up to 99 % yield, 95 % ee ). The products could be efficiently converted to a series of γ‐substituted carbonyl compounds. Pi=pipecolic acid.